Association of Adiponectin with High-Sensitivity C-Reactive Protein and Clinical Outcomes in Peritoneal Dialysis Patients: A 3.5-Year Follow-Up Study. - Chun-Wu Tung; Yung-Chien Hsu; Ya-Hsueh Shih; Chun-Liang Lin (PLoS ONE, 2015)
Adiponectin (ADPN), one of most abundant fat-derived biologically active substances, plays an important role in anti-atherosclerotic process. There are conflicting results about the impact of ADPN on cardiovascular (CV) outcomes and mortality, particularly in patients undergoing peritoneal dialysis (PD). Moreover, the relationship between ADPN and inflammatory mediators has been seldom explored in this population. Therefore, we examined the relationship between ADPN and longitudinal high-sensitivity C-reactive protein (hs-CRP) changes and investigated whether ADPN or hs-CRP levels could predict CV outcomes and mortality in prevalent PD patients after comprehensive adjustment of possible confounders.In this prospective cohort study, 78 PD patients were enrolled and followed from February 2009 to August 2012. During follow-up, CV events and all-cause mortality were recorded.The mean baseline ADPN value was 29.46±18.01 μg/ml and duration of PD treatment was 37.76±36.96 months. In multiple linear regression analysis, plasma ADPN levels positively correlated with high-density lipoprotein and negatively associated with hs-CRP, body mass index, D4/D0 glucose, triglyceride, and duration of PD treatment. After stratified by genders, the inverse association between baseline ADPN and hs-CRP was more significant in the female group. The hs-CRP levels were followed up annually and remained significantly lower in the high ADPN group in the first 2 years. Patients were then stratified into two groups according to the median ADPN value (23.8 μg/ml). The results of Kaplan-Meier survival analysis demonstrated less CV events and better survival in high ADPN group. On multivariate Cox regression analysis, only ADPN level (HR: 0.93, 95% CI: 0.88-0.98, p = 0.02), age and history of CV diseases were independent risk factors for future CV events. Furthermore, hs-CRP (HR: 1.11, 95% CI:1.001-1.22, p = 0.04) was identified as independent predictor of all-cause mortality.Serum hs-CRP levels were consistently lower in the high ADPN group during 2-year follow-up. We also demonstrated the importance of ADPN and hs-CRP in predicting CV events and all-cause mortality in PD population during 3.5-year follow-up.